2018
DOI: 10.1002/tal.1478
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table model test and numerical analysis of a long‐span cantilevered structure

Abstract: This paper presents an earthquake-resistance study program of a long-span cantilevered story building. The program consists of a shaking table test study and nonlinear seismic analysis using finite element modeling technique. A 1/30 scale model of the prototype structure was designed and manufactured and then tested via the shaking table facility. Dynamic responses of the prototype structure under different earthquake excitation loadings were simulated. Dynamic properties, acceleration, and deformation respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A reduced scale model (1/15 scale) of a typical reinforced concrete frame-core tube with a corner column removed from the first floor was designed, fabricated, and tested, and experimental results were presented regarding the seismic responses and actual process of collapse. Chen et al 12 designed and manufactured a 1/30 scale model of a long-span cantilevered story building, and then tested it via a shaking table facility to analyze the dynamic behavior, cracking pattern, and the likely governing failure mechanism of the structure. In order to study the seismic behavior of a 53-storey supertall building with a high-level transfer storey, Lu et al 13 conducted shaking table tests on a 1/30-scale model of a prototype structure.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced scale model (1/15 scale) of a typical reinforced concrete frame-core tube with a corner column removed from the first floor was designed, fabricated, and tested, and experimental results were presented regarding the seismic responses and actual process of collapse. Chen et al 12 designed and manufactured a 1/30 scale model of a long-span cantilevered story building, and then tested it via a shaking table facility to analyze the dynamic behavior, cracking pattern, and the likely governing failure mechanism of the structure. In order to study the seismic behavior of a 53-storey supertall building with a high-level transfer storey, Lu et al 13 conducted shaking table tests on a 1/30-scale model of a prototype structure.…”
Section: Introductionmentioning
confidence: 99%
“…In seismic engineering, the shaking table test can genuinely reproduce the earthquake process by loading actual seismic records and is the most direct method for studying the seismic response and failure mechanism of structures. Meanwhile, many large and complex structures use shaking table tests to study and evaluate the seismic performance of structures [1][2][3][4][5][6]. However, large-span structures located in mountain areas might need some help simulating seismic wave input due to the limitations of shaking table performance when using shaking table tests to study the seismic response of some unique structures, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Scale models are widely used for investigating the seismic behavior of different types of structures. [ 1,2 ] For long‐span or super high‐rise structures, geometric scale factors can be as large as 100 or larger. [ 3–5 ] The scale model testing relies on satisfying the similitude criteria between the model structure and the prototype structure.…”
Section: Introductionmentioning
confidence: 99%